Julio Noé y La Antología de la poesía argentina moderna (1926): un punto de inflexión en la práctica antológica en Argentina - Salazar Anglada, Aníbal (Anales de Literatura Hispanoamericana, 2008)
This work focuses on the Antología de la poesía argentina moderna. The author is the critic and historian Julio Noé. Published in 1926, and again in 1931 with a number of significant changes, this work constitutes a highly valued reference with regard to the publication of Hispanic anthologies of poetry, its influence on a number of important later works being considerable (among these works, we could highlight the anthology by Federico de Onís in 1934). The work by Noé becomes the first successful attempt to produce an anthology which, from a critical reading of the cultural past and present, displays an evolution of modern Argentinian poetry from its origins («modernismo», with Leopoldo Lugones at the forefront) to the new figures who emerged in the 1920s (avant-gardism). Nevertheless the anthologist’s rigour and his eagerness for objectivism, the close relationship between Noé and the journal Nosotros, and the generation emerging from this publication explain the privileged position of postmodernist poetry in the historicist architecture of this work.